Unwiederholbares Gottessiegel Personale Individualität nach Edith Stein - Betschart, Christof (Studia Oecumenica Friburgensia, 2021)
The individuality of the human person is central to any anthropology. For Edith Stein, the individuality or uniqueness of the person lies not only in the person's unrepeatable history, but refers also to a "personal note", which is the prerequisite for all human unfolding and which manifests itself in authentic life. From a theological perspective, all human beings "bear in their souls the special and indelible seal of God". This statement in Finite and Eternal Being leads Edith Stein to reflections related to the doctrine of imago Dei, to the theology of the Body of Christ and to Christian mysticism. In the present work, the author explores personal individuality from both a philosophical and a theological standpoint, at its point of inception in Stein's thought, and exposes the genesis of her understanding of the essential individuality of each person. This second, revised edition includes an updated status quaestionis and bibliography referencing the relevant secondary literature recently published.